Egg production monitoring in commercial laying cages via the StrongSort-EGG tracking-by-detection model - Rui Wu; Pengguang He; Yefan He; Jun Dou; Mengzui Di; Shupeng He; Khawar Hayat; Yi Zhou; Lin Yu; Jinming Pan; Hongjian Lin (Computers and Electronics in Agriculture, 2024)

Are air travelers willing to pay for mandatory carbon emission policies? Evidence from China - Bao-Jun Tang; Rui Yan; Jun-Yu Chen; Chang-Jing Ji (Sustainable Production and Consumption, 2024)

Evaluating pulmonary toxicity of PFOS and its alternative OBS using spheroids of A549 cells - Chong-Rui Yao; Yu-Xia Jiang; Si-Ying Li; Zhi-Jie Lu; Xiao-Bing Long; Na Xin; Jin-Ge Zhang; Dong-Dong Ma; Guang-Guo Ying; Wen-Jun Shi (Science of The Total Environment, 2024)

The role of biofilm in long-term corrosion of cast iron in wastewater reclaim system - Rui An; Juntao Jin; Jun Nan; Yu Tian (Journal of Water Process Engineering, 2024)

Insight into the effect of potassium amyl xanthate on copper pollution caused by chalcopyrite bio-dissolution - Rui Liao; Jun Wang; Shichao Yu; Xin Sun; Shitong Liu; Baojun Yang; Guanzhou Qiu (Journal of Environmental Management, 2024)

Visible light-assisted S-doped red mud-based Fe-Co PBA derivatives activated PMS for efficient degradation of oxytetracycline from acidic to alkaline conditions: Degradation mechanism, degradation pathways and toxicity evaluation - Shitong Liu; Jun Wang; Yang Liu; Min Cheng; Baojun Yang; Guangfu Wang; Shichao Yu; Rui Liao; Guanzhou Qiu (Journal of Environmental Chemical Engineering, 2024)

Multiomics analysis reveal the impact of 17α-Ethinylestradiol on mortality in juvenile zebrafish - Xiao-Bing Long; Chong-Rui Yao; Si-Ying Li; Jin-Ge Zhang; Zhi-Jie Lu; Dong-Dong Ma; Yu-Xia Jiang; Guang-Guo Ying; Wen-Jun Shi (Comparative Biochemistry and Physiology Part C: Toxicology & Pharmacology, 2024)

Highly stable zinc anodes enabled by a dual-function additive of in-situ film formation and electrostatic shielding - Rui-han Ji; Hao Fu; Qing Wen; Pei-Yao Li; Pei Yang; Yu-Jing Chen; He-zhang Chen; Jia-feng Zhang; Ling-jun Li; Jie-xi Wang; Qing Wu; Xia-hui Zhang; et al. (Chemical Engineering Journal, 2024)

Phylogenomic analyses and comparative genomic studies of Thermus strains isolated from Tengchong and Tibet Hot Springs, China - Inam Ullah Khan; Muhammad Saqib; Arshia Amin; Sadia Manzoor; Iftikhar Ahmed; Rui-Rui Liu; Jian-Yu Jiao; Xiao-Yang Zhi; Wen-Jun Li (Antonie van Leeuwenhoek, 2024)

Molecular characterization, spatio-temporal expression patterns of crtc2 gene and its immune roles in yellow catfish (Pelteobagrus fulvidraco) - Wan-Hong Zeng; Zheng-Yong Wen; Xiu-Ying Wei; Yu He; Luo Zhou; Peng Hu; Qing-Chao Shi; Chuan-Jie Qin; Jun Wang; Rui Li; Xiao-Ying Jing; Wei Hu; et al. (Fish & Shellfish Immunology, 2024)

Mechanism of o-cresol polymerization and its carbon recovery from aqueous solution by a cathode/Fe2+/H2O2 process - Sui-Qin Yang; Yu-Hong Cui; Wei-Jun Xue; Zheng-Qian Liu; Rui Hu; Xiao-Qian Ye (Chemical Engineering Journal, 2024)

Room temperature shape self-adjustable tough hydrogel based on multi-physical crosslinking - Jun-Bo Hou; Zhi-Chao Jiang; Yao-Yu Xiao; Rui-Dong Cheng; Yue Zhao (Chemical Engineering Journal, 2024)

External ligand-free nickel-catalyzed synthesis of polypyrazines towards stable, high-capacity and low-potential sodium ion storage - Zhihui Wang; Rui Li; Guoqing Zhao; Xiaorong Yan; Xinyu Wang; HaiPing Yu; Yuxin Hao; Yujie Dai; Huige Ma; Mengxiao Li; Hongwei Li; Mingsheng Yang; et al. (Chemical Engineering Journal, 2024)

The CYP3A inducer dexamethasone affects the pharmacokinetics of sunitinib by accelerating its metabolism in rats - Guang-rong Lu; Rui-zhen Wang; Xin-yu Zhao; Jun-er Xu; Cheng-ke Huang; Wei Sun; Rui-jie Chen; Zhe Wang (Chemico-Biological Interactions, 2024)

Probiotic nucleotides increase IL-10 expression in airway macrophages to mitigate airway allergy - Jinmei Xue; Zhizhen Liu; Bailing Xie; Rui Dong; Juan Wu; Yisha Wu; Zhihan Xu; Yuhe Tian; Yao Wei; Zhigang Geng; Lei Lu; Yu Liu; et al. (Inflammation Research, 2024)

Association of Plasma Metal Levels with Outcomes of Assisted Reproduction in Polycystic Ovary Syndrome - Dan Yin; Rui Mao; Die Wang; Ping Yu; Cuilan Zhou; Jun Liu; Suyun Li; Yulin Nie; Hongqing Liao; Cuiying Peng (Biological Trace Element Research, 2024)

Research on temperature measurement model of loose coal considering humidity using acoustic wave method - Gao-yang Qu; Jun Deng; Shuai-jing Ren; Cai-ping Wang; Ze-yang Song; Jin-rui Wang; Yu Xu; Xia-qi Zhao (Fuel, 2024)

An efficient Au/ZnO catalyst for the photocatalytic conversion of methane to formaldehyde - Yan-Qun Chen; Lei-Xin Mao; Rui-Xin Zhang; Xin-Yu Zhang; Zhi-Hua Gao; Lei Liu; Wei Huang; Zhi-Jun Zuo (Chemical Engineering Journal, 2024)

Chemical constituents from the aerial parts of Rhododendron thymifolium and its bioactivities against Tribolium castaneum, Lasioderma serricorne, and Ditylenchus destructor - Jun-Yu Liang; Ying-Ying Yang; Rui Feng; Xiao-Han Zhang; Xu-Dong Wang; Jun-Long Wang; Wei-Bao Kong; Ji Zhang (Journal of Plant Diseases and Protection, 2024)

Development and efficacy evaluation of nanoliposomes targeting CAFs-LCSCs communication for hepatocellular carcinoma treatment - Liang Kong; Yang Yu; Ru Yang; Rui-bo Guo; Lu Zhang; Jia-hua Wang; Yang Liu; Juan Zang; Chen Yang; Hui-yue Yang; Rui-jun Ju; Xue-tao Li (Chemical Engineering Journal, 2024)

Design and synthesis of ligustrazine derivatives as potential anti-Alzheimer’s agents - Xu-fei Chen; Shan-shan Li; Yu-jun Bai; Ze-feng Zhao; Ya-jun Bai; Gu Gong; Xi-rui He; Xiao-hui Zheng (Natural Product Research, 2024)

Molecular characterization of fad6 gene and its transcriptional changes in response to different initial diets and nutritional status in yellow catfish (Pelteobagrus fulvidraco) - Bo Zhou; Xiu-Ying Wei; Zheng-Yong Wen; Bin Wang; Yu-Ying Zhao; Wan-Hong Zeng; Yu He; Panita Prathomya; Yun-Yun Lv; Yan-Ping Li; Jun Wang; Rui Li; et al. (Frontiers in Marine Science, 2024)
Fatty acid desaturases (FADs) are rate-limiting enzymes for the biosynthesis of highly unsaturated fatty acids (HUFAs). As a new member of the FAD family, Fad6 and its roles remain unclear in various teleost fishes. In this study, we identified a fad6 gene from yellow catfish (yc fad6 ) and determined its spatiotemporal expression patterns and responses to different initial diets and nutritional status in yellow catfish. Our results showed that the open reading frame (ORF) of yc fad6 was 1,080 bp in length, encoding a protein of 359 amino acids. Multiple protein sequences alignment proved that fad6 is highly conserved among diverse vertebrates. Meanwhile, phylogenetic analysis revealed that Southern catfish and yellow catfish were clustered into one branch, supporting evolutionary consistence between the fad6 gene and fish morphology. Moreover, comparisons of genomic synteny and gene structure revealed functional and evolutionary conservation of the fad6 gene in various teleost fishes. Tissue distribution analysis by quantitative RT-PCR demonstrated that the yc fad6 gene was extensively expressed in examined tissues, with higher transcription levels in the heart and liver. Meanwhile, yc fad6 gene was widely expressed in various developmental stages, indicating Fad6 may play important roles in HUFA biosynthesis at early developmental stages in yellow catfish. Functional experiments verified that the transcription of yc fad6 decreased significantly with the extension of feeding time (with egg yolk or Artemia nauplii ) at the early developmental stages, indicating that a diet rich in HUFA can remarkably inhibit the transcription of yc fad6 in yellow catfish. In addition, yc fad6 transcription was significantly reduced after a short-term (24-h) or long-term food deprivation (1-week) and then continued to decrease during refeeding, suggesting that nutritional states can affect the transcription of yc fad6 , which further regulates the metabolism of HUFAs. Anyway, these fundamental findings provide basic references for further investigating evolutionary and physiological functions of the fad6 gene in yellow catfish as well as in other teleost fishes.

Heterologous expression and characterization of two delta glutathione S-transferases genes involved in imidacloprid metabolism in Grapholita molesta - Qin-Wei Pang; Wen-Jie He; Ming-Gao Li; Ming Wang; Xue-Yao Zhang; Li-Jun Zhang; Ling-Ling Gao; Rui-Yan Ma; Yan-Qiong Guo; Qin Yu (Chemosphere, 2024)

MARCH1 and MARCH2 inhibit pseudorabies virus replication by trapping the viral cell-to-cell fusion complex in trans-Golgi network - Rui Huang; Cui-Hong Rao; Yuan-Zhe Bai; Changqing Yu; Meng Chen; Jin-Mei Peng; Shi-Jia Xu; Yue Sun; Meng Fandan; Chuang Lyu; Mirwaise Khan; Tong-Qing An; et al. (Veterinary Microbiology, 2024)

An emerging antibacterial nanovaccine for enhanced chemotherapy by selectively eliminating tumor-colonizing bacteria - Linfu Chen; Zheyu Kang; Jingjing Shen; Rui Zhao; Yu Miao; Lin Zhang; Zixuan Zheng; Zhemin Zhang; Nanhui Liu; Cheng Wang; Huapan Fang; Jun Zhou; et al. (Science Bulletin, 2024)

Highly oxidized guaiane 12(8),15(6)-dilactones with neuroprotective activities from the roots of Lindera aggregata (Sims) Kosterm - Lie-Feng Ma; Si-Qing Lou; Hong-Yu Chen; Di Luo; Lu Guo; Ning-Yu Chen; Rui Wu; Luo Fang; Zha-Jun Zhan (Phytochemistry, 2024)

The mitigation of citric acid on cadmium toxicity in Iris tectorum and its effects on the composition of cell walls - Xiao-Fang Yu; Zhi-Wen Wang; Feng-Lian Chen; Mao-Lin Chen; Xin-Yu Zhang; Jun-Rui Zhang; Wen-Yu Ji; Xue Xiao; Li-Juan Yang; Ting Lei; Xi Li; Ming-Yan Jiang (International Biodeterioration & Biodegradation, 2024)

Natural aromatic extract of black tea improved the water retention of pork meat batter - Wen-ping Xu; Rui-ling Dong; Ao-jing Lv; Yu-cong Li; Li-ting Zeng; Xue-ling Gao; Jun Qi; Zhou Lin; Hui-min Yan; Chun-hui Zhang; Guo-yuan Xiong (Food Research International, 2024)

Mantle-rooted fluid pathways and world-class gold mineralization in the giant Jiaodong gold province: Insights from integrated deep seismic reflection and tectonics - Li-Qiang Yang; Jun Deng; Liang Zhang; Ai-Hua Zhao; M. Santosh; Xue-Feng Yu; Wei Yang; Da-Peng Li; Wei Shan; Dong Xie; Xiang-Dong Liu; Xue Gao; et al. (Earth-Science Reviews, 2024)

Understanding secondary particles in a regional site of Yangtze River Delta: Insights from mass spectrometric measurement - Wenfei Zhu; Jialin Shi; Hui Wang; Ying Yu; Rui Tan; Ruizhe Shen; Jun Chen; Shengrong Lou; Min Hu; Song Guo (Science of The Total Environment, 2024)

Ent-eudesmane sesquiterpenoids with anti-neuroinflammatory activity from the marine-derived fungus Eutypella sp. F0219 - Zhong-Ping Jiang; Rui Su; Meng-Ting Chen; Jun-Yi Li; Han-Yu Chen; Lu Yang; Fei-Fei Liu; Jin Liu; Cong-Jun Xu; Wan-Shan Li; Yong Rao; Ling Huang (Phytochemistry, 2024)

Establishment and characterization of a golden pompano (Trachinotus blochii) fin cell line for applications in marine fish pathogen immunology - Jin-Feng Tong; Lang Yu; Rui-Hai Gan; Li-Ping Shi; Shao-Yang Bu; Yue Gu; Xin Wen; Jun-Long Sun; Fei-Biao Song; Li Zhou; Jian-Fang Gui; Jian Luo (Fish & Shellfish Immunology, 2024)

Cadmium interacts with nitrogen level and nitrogen form to affect the growth of an invasive plant Alternanthera philoxeroides - Dan Li; Xiao-Gai Wang; Jia-Xin Yang; Yu-Fei Hu; Wen-Yue Lyu; Jun-Cai Xin; Rui Zhang; Zhi-Huan Chen; Chao Si (Aquatic Ecology, 2024)

Unveiling of dietary and gut-microbiota derived B vitamins: Metabolism patterns and their synergistic functions in gut-brain homeostasis - Qi Zhan; Rui Wang; Kiran Thakur; Jing-Yu Feng; Yun-Yang Zhu; Jian-Guo Zhang; Zhao-Jun Wei (Critical Reviews in Food Science and Nutrition, 2024)

Effect of sludge redistribution strategy on stability of partial nitrification-anammox process: Further exploration of the potential value of sludge - Peng Wang; Rui Ou; Jun Tan; Ning Li; Min Zheng; Qinghai Jin; Jin Yu; Di He (Chemosphere, 2024)

Computational-aided analysis of the pathway and mechanism of dichloroacetonitrile formation from phenylalanine upon chloramination - Rui Yu; Yunkun Qian; Yanan Chen; Yijun Shi; Jun Guo; Dong An (Science of The Total Environment, 2024)

Carboxymethyl chitosan-based hydrogel-Janus nanofiber scaffolds with unidirectional storage-drainage of biofluid for accelerating full-thickness wound healing - Xinhao Chen; Hui Huang; Xinru Song; Ting Dong; Jiafei Yu; Jieyan Xu; Rui Cheng; Tingting Cui; Jun Li (Carbohydrate Polymers, 2024)

Brain-Derived Exosomal CircRNAs in Plasma Serve as Diagnostic Biomarkers for Acute Ischemic Stroke - Xinli Jiang; Rui Zhang; Geng Lu; Yu Zhou; Jianfeng Li; Xinrui Jiang; Shuangshuang Gu; Hongwei Liang; Jun Wang (Journal of Neuroimmune Pharmacology, 2024)

DeepWMH: A deep learning tool for accurate white matter hyperintensity segmentation without requiring manual annotations for training - Chenghao Liu; Zhizheng Zhuo; Liying Qu; Ying Jin; Tiantian Hua; Jun Xu; Guirong Tan; Yuna Li; Yunyun Duan; Tingting Wang; Zaiqiang Zhang; Yanling Zhang; et al. (Science Bulletin, 2024)

A renal-targeted gene delivery system derived from spermidine for arginase-2 silencing and synergistic attenuation of drug-induced acute kidney injury - Xu-Rui Gu; Kun Liu; Yi-Xuan Deng; Bi-Xiao Xiang; Ling-Yun Zhou; Wen-Jun Yin; Jia-Xin Huang; Ying-Cai Meng; Dian-Ke Li; Rui-Man Que; Zhi-Yao Tang; Guang-Liang Zhou; et al. (Chemical Engineering Journal, 2024)

Hollow AMn2O4-δ (A = Co, Zn, Ni) nanotube for direct photo-oxidation of methane to C1 and C2 alcohols at atmospheric pressure and room temperature - Jun Duan; Shiying Fan; Xinyong Li; Jing Wang; Chunpeng Bai; Shixuan Yu; Weitong Ling; Rui Tian; Dongke Zhang (Chemical Engineering Journal, 2024)

Modeling nitrogen removal performance based on novel microbial activity indicators in WWTP by machine learning and biological interpretation - Yadan Yu; Hao Zeng; Liyun Wang; Rui Wang; Houzhen Zhou; Liang Zhong; Jun Zeng; Yangwu Chen; Zhouliang Tan (Journal of Environmental Management, 2024)

Regulatory effect of trehalose metabolism on chitin synthesis in Spodoptera frugiperda (J. E. Smith) (Lepidoptera: Noctuidae) as determined using RNAi - Yan-qi Yang; Yu-jian Liang; Jun-rui Zhi; Ding-yin Li; Cao Li (Journal of Asia-Pacific Entomology, 2024)

Promotion of anaerobic biodegradation of azo dye RR2 by different biowaste-derived biochars: Characteristics and mechanism study by machine learning - Yu-Qian Wang; Jie Ding; Ji-Wei Pang; Chuan-Dong Wu; Han-Jun Sun; Rui Fang; Nan-Qi Ren; Shan-Shan Yang (Bioresource Technology, 2024)

Function-oriented bifunctional Mg & MoP modified polymeric carbon nitride for selective photoreduction CO2 to CH4 - Jun-ying Tang; Wei-guo Pan; Yu-lian He; Tian-shuo Zhao; Qing-shan Wang; Rui-tang Guo (Chemical Engineering Journal, 2024)

The lncRNA20718-miR6022-RLPs module regulates tomato resistance to Phytophthora infestans - Jia-hui Zhang; Hong-bo Wei; Yu-hui Hong; Rui-rui Yang; Jun Meng; Yu-shi Luan (Plant Cell Reports, 2024)

Pathways for regions to achieve carbon emission peak: New insights from the four economic growth poles in China - Yu-Jie Hu; Fali Duan; Honglei Wang; Chengjiang Li; Rui Zhang; Bao-Jun Tang (Science of The Total Environment, 2024)

Polysulfide regulation by defect-modulated Ta3N5− electrocatalyst toward superior room-temperature sodium-sulfur batteries - Zhen Zhang; Dan Luo; Jun Chen; Chuyin Ma; Matthew Li; Haoze Zhang; Renfei Feng; Rui Gao; Haozhen Dou; Aiping Yu; Xin Wang; Zhongwei Chen (Science Bulletin, 2024)

Synergizing policies for carbon reduction, energy transition and pollution control: Evidence from Chinese power generation industry - Yu-Jie Hu; Rui Zhang; Honglei Wang; Chengjiang Li; Bao-Jun Tang (Journal of Cleaner Production, 2024)

Tree-ring structured phase change materials with high through-plane thermal conductivity and flexibility for advanced thermal management - Wan-jun Jiang; Rui-qing Wang; Ting-yu Zhu; Mai Feng; De-xiang Sun; Jing-hui Yang; Xiao-dong Qi; Yong Wang (Chemical Engineering Journal, 2024)

Sulfite activation of Fe-Mn bimetallic oxides for rapid oxidative removal of As(III) in water: Involvement of active Mn(III) - Guiyuan Cai; Yu Tian; Lipin Li; Wenxuan Zhang; Rui Huang; Jun Zhang; Qinyu Wang; Hua Xu; Yifeng Zhang (Chemical Engineering Journal, 2024)